Studi Bioinformatika Kandungan Curzerene Pada Daun Dewandaru (Eugenia uniflora Linn.) Sebagai Antikanker Prostate Melalui Pensinyalan PI3K: Studi Bioinformatika Kandungan Curzerene Pada Daun Dewandaru (Eugenia uniflora Linn.) Sebagai Antikanker Prostate Melalui Pensinyalan PI3K - Andriese, Ni Putu Sri Ayu Sevilla Andriese; Santoso, Puguh; Ari Candra, Agung; Surya Rahadi, I Wayan (Usadha, 2023)
One of the original Indonesian plants that has medicinal properties is Dewandaru (Eugenia uniflora Linn.). Dewandaru shows cytotoxic activity against cancer cells so it has the potential to be used as a drug preparation. The potential compound from the leaves of Dewandaru is Curzerene. This research was conducted to identify the interaction between the compounds of dewadaru leaves and PI3K receptors in prostate cancer. This study uses a computational method known as molecular docking. Bond energies, visualization of bonds, and types of bonds between compounds and receptors were observed. The PI3K receptor has fulfilled the method validation test requirements. The results showed that compounds from the dewadaru plant could inhibit one target protein from prostate cancer which was expressed with the lowest ∆Gbinding value, namely Curzerene compound (-7.65 kcal/mol) in PI3K protein. The interaction between Curzerene compounds has a lower binding energy value when compared to the original ligands at the PI3K receptor. Thus, it can be concluded that the Curzerene compound in the dewadaru plant used in the study has a good interaction with the PI3K receptor in prostate cancer. This compound has the potential to be developed as an anticancer drug. It is necessary to carry out in vivo testing and modification of the structure of the compound so that it can be used as an effective anticancer therapy in prostate cancer. Keywords: Prostate cancer, Curzerene, Dewandaru leaves, In silico